Efficacy and Safety of Direct Oral Anticoagulants in Patients with Diabetes and Nonvalvular Atrial Fibrillation: Meta-Analysis of Observational Studies - Bo Cao; Xingcan Yao; Lifang Zhang; Xiaobo Hu; Min Chen; Mingfeng Shen; Lan Xu (Hindawi-Wiley, 2021)
Background. This meta-analysis was performed to compare the efficacy and safety of direct oral anticoagulants (DOACs) with vitamin K antagonists (VKAs) for stroke prevention in real-world patients with diabetes and nonvalvular atrial fibrillation (NVAF) through observational studies. Methods. PubMed, Embase, and Web of Science databases were searched up to August 2020 for eligible studies. Outputs were presented as risk ratios (RRs) and corresponding 95% confidence intervals (CIs) by using a random-effect model. Results. Seven observational studies involving 249,794 diabetic NVAF patients were selected. Compared with VKAs, the use of DOACs was associated with significantly reduced risks of stroke (RR=0.56, 95% CI 0.45-0.70; p<0.00001), ischemic stroke (RR=0.61, 95% CI 0.48-0.78; p<0.0001), stroke or systemic embolism (SSE) (RR=0.81, 95% CI 0.68-0.95; p=0.01), myocardial infarction (RR=0.69, 95% CI 0.55-0.88; p=0.002), major bleeding (RR=0.75, 95% CI 0.63-0.90; p=0.002), intracranial hemorrhage (RR=0.50, 95% CI 0.44-0.56; p<0.00001), and major gastrointestinal bleeding (RR=0.77, 95% CI 0.62-0.95; p=0.02), and a borderline significant decrease in major adverse cardiac events (RR=0.87, 95% CI 0.75-1.00; p=0.05) in NVAF patients with diabetes. Conclusion. For patients with NVAF and diabetes in real-world clinical settings, DOACs showed superior efficacy and safety profile over VKAs and significantly reduced risks of stroke, ischemic stroke, SSE, myocardial infarction, major bleeding, intracranial hemorrhage, and major gastrointestinal bleeding.